A study on the pattern of antibiotic resistance on different infective organisms in a tertiary care hospital - K. S., Thrupthi; G., Janavi; M. M., Sachin Nayaka; Sivakumar, Anjaly (International Journal of Research in Medical Sciences, 2025)
Background: A serious problem for global health, antibiotic resistance raises morbidity, mortality, and medical expenses. A clear understanding of local resistance patterns is required to maximize empirical therapy and infection control. Objectives of the study was to identify infective organisms and determine their antibiotic resistance profiles in a tertiary care hospital. To assess the resistance patterns across various antibiotic classes. Methods: A cross-sectional study was conducted in a tertiary care center. Clinical specimens (pus, urine, sputum, blood, and tissue) were obtained and processed using standard microbiological culture techniques. Isolates were identified, and antibiotic susceptibility testing was performed via the disc diffusion method in accordance with Clinical and Laboratory Standards Institute (CLSI) guidelines. Results: As a result, the present data analysis releaving that the culture positive was seen more in the 46-65 age range and with a higher propotion of females. The majority of the isolated organisms were Escherichia coli (23%), Staphyloccus aureus (21%), Klebisella pneumonia (21%), Pseudomonas aeruginosa (11%). The sample that grew organisms were pus (65), urine (13), sputum (17), blood (3), tissue (2). Conclusions: The prevalence of drug-resistant infections, particularly in patients aged 46–65 and among females, underscores the importance of routine antimicrobial surveillance. E. coli’s high cefuroxime resistance and maintained amikacin susceptibility highlight the need for evidence-based empirical therapy. Strengthening hospital-based antibiotic stewardship programs is recommended to curb the spread of resistance.